Is Modern Latin American Urban Planning? (Andamios, Revista de Investigación Social, 2013)
The Latin American urbanism is not modern fundamentally because the notion of theory with which it thinks and constructs the city is not the modern concept of theory. In the neoliberal capitalist economy model as a frame for the urban reflection on Latin America, what prevails is the lack of interest for the theory and the fight against its modern conception from the pragmatism, the postmodernism, and the cultural studies. Therefore, from the anti modern urbanism we should not expect interest for the past, the future, the construction of community or the inclusion of the poor, but urbanization according to the interests of a minority in detriment of the majority’s interests.
Keywords: Modernity; Theory; Pragmatism; Postmodernism; Culturalism